THE ROLE OF THE LEADER IN IMPROVING THE ORGANIZATION PERFORMANCE OF THE INVESTMENT OFFICE AND ONE-STOP INTEGRATED SERVICES IN SUKABUMI CITY - Lestari, Dinda; Meigawati, Dine; Sampurna, Rizki Hegia (DIA: Jurnal Administrasi Publik, 2023)
A success fluency in an organization is largely determined by individual performance and organizational performance in achieving the goals of the organization. This is where the role of the leader is very important and much needed, leadership led by a reliable leader will help build the organization or agency he leads. To find out the role of the leader in the The Investment Office And One-Stop Integrated Services In Sukabumi City, researchers used the theory of Henry Mintzberg who argued that there were three main roles played by every leader regardless of the hierarchical location, namely The Interpersonal Role, The Informational Role, and The Decisional Role. The research method used is a qualitative research method, data collection techniques used include observation, interviews, and documentation. The results of the research show that each role fulfills the criteria of being e leader, capable of playing a role in directing and motivating employees, capable of playing a role in providing information and being a source of information, and capable of playing in important role in terms of decision making.